Emerging role of microRNA 628-5p as a novel biomarker for cancer and other diseases - Leslimar Rios-Colon; Gagan Deep; Deepak Kumar (Tumor Biology)
MicroRNAs are a family of small, single-stranded RNAs that have key roles in regulating multiple signaling pathways within a cell. Studies have implicated aberrant expression of microRNAs in the development and progression of several pathologies including cancer. MicroRNAs are relatively stable and readily available in body fluids and tissues, making them desirable biomarkers for prognostic and diagnostic purposes in an array of diseases. MicroRNA 628 (5p/3p variants) is located in the 15q21.3 cancer-related region, and evidence suggests its association with various pathologies. The -5p mature variant, microRNA 628-5p, has been reported to be differentially expressed in various cancers, and its expression has been mostly associated with tumor suppression but there are few reports identifying its role in cancer progression. Several studies have also suggested its utility in diagnosis and prognosis of various cancers. Dysregulation of microRNA 628-5p has also been implicated in embryonal implantation defects, autism, immune modulation, myogenesis, cardiovascular disease, viral infection, and skeletal muscle repair. Here, we have provided a comprehensive review on available literature explaining the role of microRNA 628-5p as a potential cancer biomarker as well as briefly describe its function in other diseases and normal physiological conditions.